DIFFERENTIAL SUSCEPTIBILITY OF HUMAN SP-B GENETIC VARIANTS ON LUNG INJURY CAUSED BY BACTERIAL PNEUMONIA AND THE EFFECT OF A CHEMICALLY MODIFIED CURCUMIN. Issue 4 (April 2016) - Xu, Yongan; Ge, Lin; Abdel-Razek, Osama; Jain, Sumeet; Liu, Zhiyong; Hong, Yucai; Nieman, Gary; Johnson, Francis; Golub, Lorne M.; Cooney, Robert N.; Wang, Guirong
Abstract : ABSTRACT: Staphylococcus aureus is a common cause of nosocomial pneumonia frequently resulting in acute respiratory distress syndrome (ARDS). Surfactant protein B (SP-B) gene expresses two proteins involved in lowering surface tension and host defense. Genotyping studies demonstrate a significant association between human SP-B genetic variants and ARDS. Curcumins have been shown to attenuate host inflammation in many sepsis models. Our hypothesis is that functional differences of SP-B variants and treatment with curcumin (CMC2.24) modulate lung injury in bacterial pneumonia. Humanized transgenic mice, expressing either SP-B T or C allele without mouse SP-B gene, were used. Bioluminescent labeled S. aureus Xen 36 (50 μL) was injected intratracheally to cause pneumonia. Infected mice received daily CMC2.24 (40 mg/kg) or vehicle alone by oral gavage. Dynamic changes of bacteria were monitored using in vivo imaging system. Histological, cellular, and molecular indices of lung injury were studied in infected mice 48 h after infection. In vivo imaging analysis revealed total flux (bacterial number) was higher in the lung of infected SP-B-C mice compared with infected SP-B-T mice ( P < 0.05). Infected SP-B-C mice demonstrated increased mortality, lung injury, apoptosis, and NF-κB expression compared with infected SP-B-T mice. Compared with controls, CMC2.24 treatment significantly reduced the following: mortality, total bacterial flux and lung tissue apoptosis, inflammatory cells, NF-κB expression ( P < 0.05), and MMPs-2, -9, -12 activities ( P < 0.05). We conclude that mice with SP-B-C allele are more susceptible to S. aureus pneumonia than mice with SP-B-T allele, and that CMC2.24 attenuates lung injury thus reducing mortality.